2018
DOI: 10.1002/mame.201800313
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Coatings for Improved Performance of Electrical Insulators

Abstract: Dielectric strength of electrical insulators is adversely affected by both wet conditions and surface roughness due to accelerated dielectric breakdown. While textured superhydrophobic coatings (i.e., coatings that are extremely repellent to water) can prevent the accumulation of water and help retain the dielectric strength of insulators under wet conditions, it is unclear whether or not the presence of texture (i.e., surface roughness) allows the retention of the dielectric strength of insulators. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…17 Composite insulator, as the best choice in polluted areas, can effectively reduce the occurrence of flashover accidents. At present, the commonly used preparation methods of super-hydrophobic surface of composite insulators mainly include: laser engraving method, 18,19 template method, 14,20 coating method, 21,22 spraying method, 23,24 mixing method, 25,26 and so forth. Wang et al 14 prepared a superhydrophobic insulator by using stainless steel mesh as a template and the hydrophobic effect was obviously improved.…”
Section: Introductionmentioning
confidence: 99%
“…17 Composite insulator, as the best choice in polluted areas, can effectively reduce the occurrence of flashover accidents. At present, the commonly used preparation methods of super-hydrophobic surface of composite insulators mainly include: laser engraving method, 18,19 template method, 14,20 coating method, 21,22 spraying method, 23,24 mixing method, 25,26 and so forth. Wang et al 14 prepared a superhydrophobic insulator by using stainless steel mesh as a template and the hydrophobic effect was obviously improved.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hierarchically structured surfaces that possess more than one scale of texture can cause a reduction in solid-liquid interfacial area and interaction, which can also enhance superhydrophobicity. 8,11 Because of the low reactivity and ultra-low wettability, superhydrophobic surfaces have been widely applied to many fields, such as anti-fouling, 12,13 self-cleaning, [14][15][16] liquid drag reduction, [17][18][19] and icephobicity. [20][21][22] Superhydrophobic surfaces have also been investigated based on their hemocompatibility for applications in the field of biology and medicine, [23][24][25] because they significantly reduce the blood-material interfacial contact area, thereby reducing the area available for protein adsorption and blood cell or platelet adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in our group have focused on the electric field-driven self-propelled motion of water droplets on a superhydrophobic surface [20], and the droplet condensation on superhydrophobic surfaces under AC electric fields has also been investigated [21]. Vallabhuneni et al showed that superhydrophobic polydimethylsiloxane sheets could maintain dielectric strength under wet conditions [22]. Jin et al performed a numerical simulation to discuss the influence of the contact angle, volume, and location of water droplets, and the results indicated that the superhydrophobic surface showed excellent electric field shielding performance [23].…”
Section: Introductionmentioning
confidence: 99%